A Nepal Perspective on Closing the Carbon Cycle Pathways to De-fossilize Difficult-to-Electrify Sectors in a Hydropower-Dominated Economy - Sigdel, Shobha; Shrestha, Rabin (Journal of Advanced College of Engineering and Management, 2026)
Urgent decarbonization of energy systems, industrial processes and transportation is necessary to mitigate GHG emissions. Though Nepal generates more than 95% of electricity from hydropower, still there are difficult-to-electrify sectors like transportation, fertilizer production, cement and brick industries, which are fossil fuels dominated. This dependency causes increase in fuel imports, emissions, and climate risks. This paper studies how Nepal can move forward towards a circular carbon economy by adopting the principle of closing the carbon cycle, originally developed in the US context, to Nepal’s hydropower-dominated and resource-constrained economy. Using a qualitative and systems-oriented approach based on secondary literature, policy documents, and sectoral reports, the study identifies key scientific and technological opportunities, including green hydrogen and ammonia production from surplus hydropower, carbon capture and utilization in cement and brick industries, and waste-to-energy systems for urban resilience. Based on this adaptation, a Nepal-specific conceptual framework is proposed to connect energy, industry, agriculture, and waste systems so that carbon can be reused across multiple applications before final disposal. The paper also highlights policy implications, investment considerations, and a phased research and innovation roadmap emphasizing enabling regulations, financial incentives, pilot projects, and inclusive governance. The study concludes that Nepal can position itself as a model for decentralized, low-carbon development by strategically aligning renewable electricity, carbon reuse pathways, and sector-specific transition policies.